An Analysis of Figurative Language used in World of Warcraft Game Reviews - Marco Tomasowa; Farida Agoes (Jurnal Bahasa Inggris Terapan, 2022)
This study aims to investigate the types of figurative language used in online reviews of a game. The method applied in the study was qualitative. The data were obtained from ten online reviews of the World of Warcraft game found on the internet. The data were analyzed using a stylistic approach. The results show that four types of figurative language tend to be used in the reviews. They are hyperbole (40%), personification (24%), simile (23%), and metaphor (13%).